Tinjauan Terhadap Wewenang Komisi Informasi Dalam Menguji Keputusan Tata Usaha Negara - Rahmat, Rahmat; Yusuf, Muhammad (Jurnal Litigasi Amsir, 2023)
This research aims, firstly, to understand the implementation of duties and authority of the Information Commission in resolving public information disputes in the form of Decisions of State Administrative Officers at the West Sulawesi Provincial Information Commission. Secondly, to determine the legal sources for the Information Commission in resolving public information disputes in the form of Decisions of State Administrative Officers. This type of research is normative legal research, which utilizes a statutory approach and a case approach. This research is also commonly referred to as library research (law in book). The research techniques used are interviews, observations, and literature reviews. The results of this research are as follows: The implementation of duties and authority of the Information Commission in resolving public information disputes in the form of Decisions of State Administrative Officers at the West Sulawesi Provincial Information Commission has been carried out based on Law Number 14 of 2008 concerning public information disclosure. The Information Commission has the authority to resolve information disputes with Decisions of State Administrative Officers as the object. The legal sources for the Commissioners’ Panel in deciding disputes with Decisions of State Administrative Officers as the object. However, even though the object of the dispute is a Decision of State Administrative Officers, the authority of the Information Commission to adjudicate is limited to the aspect of information disclosure, not the legality of the State Administrative Officer’s decision